Leader humility and creativity: A systematic literature review - Hendryadi, Hendryadi (Jurnal Akuntansi dan Manajemen, 2024)
This systematic literature review synthesizes empirical evidence on the relationship between leader humility and creativity at the individual and team levels. Data were collected from the Scopus database using PRISMA procedures, including 17 empirical articles. Data were analyzed thematically to identify patterns, mediating mechanisms, moderating variables, and theoretical frameworks. The findings show that leader humility is positively related to both individual and team creativity. Key mediating mechanisms include psychological safety, psychological capital, and creative self-efficacy, while significant moderating variables include power distance, task interdependence, and top management support. Dominant theoretical frameworks used are social learning theory, social information processing theory, social cognitive theory, and social exchange theory. This review is the first comprehensive synthesis, exclusively based on 17 recent empirical articles (2017–2023), to map the research landscape on leader humility and creativity and to formulate an integrated future research agenda